Crime in England 1688 - 1815 - Cox, David J. (History of crime in the UK and Ireland, 2014)
The impact of historical developments on the criminal justice system -- Crime, 'traditional' and 'new' -- Capturing the criminal -- Punishment -- Gender and the criminal justice system -- Crime in contemporary literature and culture -- Review and conclusion : beyond the eighteenth century